Pendekatan Gamifikasi Non-Digital Untuk Meningkatkan Motivasi Ekstrinsik dan Produktivitas Karyawan Divisi Produksi - Fitriyadi Salam; Hilmi Aulawi; Risa Aisyah (Institut Teknologi Garut, 2026)
This study was motivated by the low level of extrinsic motivation and fluctuating productivity of employees in the production division of an instant food company with limited technological infrastructure. The study aims to design and test a non-digital gamification system based on game elements such as points, badges, and leaderboards to increase employees' extrinsic motivation and work productivity. This study uses a mixed-method approach with an exploratory sequential design. The initial stage involved in-depth interviews and thematic analysis to formulate gamification interventions. Next, the quantitative stage was carried out by distributing Likert questionnaires to production employees. The data were analyzed using PLS-SEM. The results showed that the application of non-digital gamification significantly increased extrinsic motivation (B=0.736; p<0.001) and employee productivity (B=0.601; p=0.008). However, extrinsic motivation did not significantly affect productivity (p=0.475) and did not mediate the gamification-productivity relationship. These findings provide empirical contributions to HR management with applicable gamification strategies, as well as implications for companies to implement game elements in reward systems without relying on advanced technology.